A global regulator of secondary metabolite production in Pseudomonas fluorescens Pf-5. - Corbell, N (1995)
Mutations in the apdA (for antibiotic production) gene of the plant root-colonizing bacterium Pseudomonas fluorescens Pf-5 pleiotropically abolish the production of an array of antibiotics, including pyrrolnitrin, pyoluteorin, and 2,4-diacetylphloroglucinol, as well as the production of tryptophan side chain oxidase, hydrogen cyanide, and an extracellular protease. The lack of production of secondary metabolites by ApdA- mutants was correlated with the loss of inhibition of the phytopathogenic fungus Rhizoctonia solani in culture. Sequencing of the apdA region identified an open reading frame of 2,751 bp. The predicted amino acid sequence of the apdA gene contains conserved domains of the histidine kinases that serve as sensor components of prokaryotic two-component regulatory systems. The apdA nucleotide and predicted amino acid sequences are strikingly similar to the sequences of lemA and repA, genes encoding putative sensor kinases that are required for the pathogenicity of Pseudomonas syringae pv. syringae and Pseudomonas viridiflava, respectively. Introduction of the cloned apdA+ gene restored the wild-type phenotype to both LemA- mutants of P. syringae and ApdA- mutants of Pf-5. The 101-kDa ApdA protein reacted with an anti-LemA antiserum, further demonstrating the similarity of ApdA to LemA. These results show that apdA encodes a putative sensor kinase component of a classical two-component regulatory system that is required for secondary-metabolite production by P. fluorescens Pf-5.